CESAM – Code for European severe accident management, EURATOM project on ASTEC improvement. (June 2018) - Nowack, H.; Chatelard, P.; Chailan, L.; Hermsmeyer, St.; Sanchez, V.; Herranz, L.
Highlights: ASTEC has been improved on phenomena relevant for the Fukushima accidents. Realistic modelling of BWR and PHWR type reactors has been implemented. Extensive validation of severe accident phenomena models has been performed. Input decks for NPP-types under operation in Europe have been created and applied. Abstract: The CESAM FP7 project (Van Dorsselaere et al., 2015) of EURATOM has been conducted from April 2013 until March 2017 in the aftermath of the Fukushima Dai-ichi accidents. Nineteen international partners from Europe and India, including the European Joint Research Centre, have participated under the coordination of GRS and with a strong involvement of IRSN that were both ASTEC code developers. The Project objectives were: to understand all relevant phenomena during the Fukushima Dai-ichi accidents and their importance for Severe Accident Management (SAM) measures; and to improve the ASTEC computer code to simulate plant behaviour throughout accident sequences including SAM measures. The starting point was the analysis of current SAM measures implemented in European nuclear power plants. To achieve these goals, simulations of relevant experiments that allow a solid validation of the ASTEC code against single and separate effect tests have been conducted. Covered validation topics in the CESAM project have been grouped in 9 different areas among which are re-flooding of degraded cores, pool scrubbing, hydrogen combustion, or spent fuel pool behaviour. Furthermore, modelling improvements have been implemented in the current ASTEC V2.1 series for the estimation of source term consequences in the environment and the prediction of plant status in emergency centres. Finally, ASTEC reference input decks have been created for all reactor types operated in Europe today as well as for spent fuel pools. These reference input decks generically describe plant types like PWR, VVER, PHWR, and BWR without defining proprietary data of a special plant and they account for the best recommendations from code developers and users. In addition, a generic input deck for a spent fuel pool was elaborated. These input decks can be used as basis by all (and especially new) ASTEC users in order to understand code basic requirements and model features and to implement the specificities of their own NPP type. Based on these generic inputs, benchmark calculations have been performed with other codes (such as MELCOR, MAAP, ATHLET-CD, COCOSYS…) with a focus on applicability of ASTEC models to currently implemented SAM measures. This article provides a final summary of the CESAM project. Therefore, an overview of the improved modelling capabilities of the recent ASTEC V2.1 version is given followed by the validation status of ASTEC V2.1 as concluded after CESAM. Further, plant applications performed by CESAM partners will be summarized with a special focus on simulation of SAM measures in various NPP types, and insights gained on SAM measures will be derived.